Measurement of fracture parameters based upon digital image correlation and virtual crack closure techniques. (1st November 2021) - Huo, Xintao; Luo, Quantian; Li, Qing; Sun, Guangyong
Abstract: This study aims to develop a novel approach to characterizing fracture parameters of cracked structures made of composite laminates and brittle adhesive joints by using digital image correlation (DIC) and virtual crack closure technique (VCCT). The parameters of mixed-mode fracture can be identified properly using the present method, which allows characterizing the important fracture properties of composite laminates, such as mixed parameter η in the Benzeggagh-Kenane fracture criterion. The energy release rates (ERR) of cracked structure is formulated in a context of linear elastic fracture mechanics (LEFE) based upon DIC measurement, finite element analysis and VCCT. Explicit formulae of energy release rates are derived in terms of the full-field displacements measured from DIC. To verify the effectiveness of the proposed method, the joint specimens are prepared and tested subject to the double cantilever beam, end-notched flexure and single-leg bending conditions, respectively. Energy release rates and fracture toughness for each specimen are obtained by using the proposed approach, which are compared with those obtained from the analytical solutions and finite element analysis (FEA). For showcasing the potential of further applications, the present method is also employed to acquire the fracture parameters of composite laminate, which contains both inter-laminar and intra-laminar fracture modes. The new parametric identification approach exhibits excellent agreement with the other methods. The proposed DIC - VCCT based method demonstrates the effectiveness for determining the energy release rates of various cracked structures. Graphical abstract: Image 1